2003
DOI: 10.1111/j.1151-2916.2003.tb03347.x
|View full text |Cite
|
Sign up to set email alerts
|

Singular Grain Boundaries in Alumina and Their Roughening Transition

Abstract: The shapes and structures of grain boundaries formed beto its step free energy, 5 ' 6 it becomes 0 when the roughening tween the basal (0001) surface of large alumina grains and transition occurs. The roughening transition is thus characterized randomly oriented small alumina grains are shown to depend by the shape change from flat to curved. A crystal surface with an on the additions of SiO 2 , CaO, and MgO. If a sapphire crystal orientation which does not appear in the equilibrium shape can is sintered at 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
40
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 64 publications
3
40
0
Order By: Relevance
“…[27][28][29] In some cases, a glassy film has been observed on these large facets, 5,7,30 which may be related to Ca segregation, 31 but other studies have found no evidence for such a film. 2,32 In contrast, further doping of CaO/SiO 2 -doped alumina with MgO hinders faceting and also inhibits AGG. 2,32 Recently, an alternative theory for AGG has been advanced, namely that under conditions in which most solid-liquid surfaces or grain boundaries are strongly faceted, the growth is limited by the sparse number of surface ledges or grain boundary dislocations to serve as attachment sites.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[27][28][29] In some cases, a glassy film has been observed on these large facets, 5,7,30 which may be related to Ca segregation, 31 but other studies have found no evidence for such a film. 2,32 In contrast, further doping of CaO/SiO 2 -doped alumina with MgO hinders faceting and also inhibits AGG. 2,32 Recently, an alternative theory for AGG has been advanced, namely that under conditions in which most solid-liquid surfaces or grain boundaries are strongly faceted, the growth is limited by the sparse number of surface ledges or grain boundary dislocations to serve as attachment sites.…”
mentioning
confidence: 99%
“…2,32 In contrast, further doping of CaO/SiO 2 -doped alumina with MgO hinders faceting and also inhibits AGG. 2,32 Recently, an alternative theory for AGG has been advanced, namely that under conditions in which most solid-liquid surfaces or grain boundaries are strongly faceted, the growth is limited by the sparse number of surface ledges or grain boundary dislocations to serve as attachment sites. In such a situation, a large grain should have a higher probability of forming such line defects and would tend to grow correspondingly quicker.…”
mentioning
confidence: 99%
“…The low index grain boundaries were observed in several metals 8,9) and oxides [10][11][12][13][14][15][16] by normal or high resolution transmission electron microscopy (TEM). But the reported results were often limited to one or two grain boundary segments and it was therefore difficult to judge the frequency of their occurrence.…”
Section: Introductionmentioning
confidence: 99%
“…In polycrystalline Au, Ichinose and Ishida 8) reported that about 30% of the grain boundaries observed were low index grain boundaries but the macroscopic shapes of the boundaries were not described. In Ni, 17) 316L stainless steel, 18) a Ni-base superalloy, 19) Si-iron 20) and alumina, 16) grain boundaries with hill-and-valley (h&v) shapes were observed. Although the segments of these boundaries were likely to be singular, the orientations of their boundary planes were not determined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation